Synergistic photomagnetic effects in coordination polymer heterostructure particles of Hofmann-like Fe(4-phenylpyridine)2[Ni(CN)4]·0.5H2O and K0.4Ni[Cr(CN)6]0.8·nH2O. Issue 42 (3rd August 2016) - Gros, Corey R.; Peprah, Marcus K.; Felts, Ashley C.; Brinzari, Tatiana V.; Risset, Olivia N.; Cain, John M.; Ferreira, Cauê F.; Meisel, Mark W.; Talham, Daniel R.
Abstract : A coordination polymer heterostructure exhibits light-switchable magnetism with the photoevent in one component influencing the magnetization of the other. Abstract : New nanometer scale heterostructure particles of the two-dimensional Hofmann-like Fe(ii ) spin-crossover network, Fe(phpy)2 [Ni(CN)4 ]·0.5H2 O {phpy = 4-phenylpyridine}, and the Prussian blue analogue K0.4 Ni1.0 [Cr(CN)6 ]0.8 · n H2 O (NiCr-PBA) have been developed, exhibiting synergistic photomagnetic effects, whereby the LIESST (light-induced electron spin-state trapping) effect in the Hofmann-like material induces a magnetization change in the NiCr-PBA. A variety of microscopic and spectroscopic techniques demonstrate the heterogeneous growth of the NiCr-PBA on the Hofmann seed particles and show the Hofmann compound retains its thermal and photoinduced spin transition properties in the heterostructure. The photoinduced magnetization change in the NiCr-PBA network arises from coupling of the two lattices despite dissimilar structure types. Isothermal magnetization minor hysteresis loop studies at 5 K show light absorption leads to changes in the local anisotropy of NiCr-PBA magnetic domains, providing direct evidence for a general magnetomechanical mechanism of light-switchable magnetism in coordination polymer heterostructures combining a photoactive material with a magnet.